2023
DOI: 10.3390/ijms24087062
|View full text |Cite
|
Sign up to set email alerts
|

3D-Cultured Adipose-Derived Stem Cell Spheres Using Calcium-Alginate Scaffolds for Osteoarthritis Treatment in a Mono-Iodoacetate-Induced Rat Model

Abstract: Osteoarthritis (OA) is a degenerative disease that causes pain, cartilage deformation, and joint inflammation. Mesenchymal stem cells (MSCs) are potential therapeutic agents for OA treatment. However, the 2D culture of MSCs could potentially affect their characteristics and functionality. In this study, calcium-alginate (Ca-Ag) scaffolds were prepared for human adipose-derived stem cell (hADSC) proliferation with a homemade functionally closed process bioreactor system; the feasibility of cultured hADSC sphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
(45 reference statements)
0
2
0
Order By: Relevance
“… 22 The isolation of ADSCs is minimally invasive and cells are easily isolated from subcutaneous fat. 84 Additionally, ADSCs have low immunogenic reactivity due to the limited expression of immunogenic antigens such as CD40, CD40L, CD80, and CD86. 85 A study conducted by Lin et al investigated the application of ADSCs in calcium-alginate hydrogel spheres and applied to a monosodium iodoacetate (MIA)-induced OA in vivo model in rats.…”
Section: Cell Therapies For Cartilage Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“… 22 The isolation of ADSCs is minimally invasive and cells are easily isolated from subcutaneous fat. 84 Additionally, ADSCs have low immunogenic reactivity due to the limited expression of immunogenic antigens such as CD40, CD40L, CD80, and CD86. 85 A study conducted by Lin et al investigated the application of ADSCs in calcium-alginate hydrogel spheres and applied to a monosodium iodoacetate (MIA)-induced OA in vivo model in rats.…”
Section: Cell Therapies For Cartilage Regenerationmentioning
confidence: 99%
“…It was reported that the OA score was significantly reduced in the spheroid group as well. 84 A clinical study using the intra-articular injection of autologous ADSCs demonstrated an improvement in pain, function and mobility in patients with severe knee OA. 83 A meta-analysis comparing ADSCs and BM-MSCs found that ADSCs had a statistically significant and consistent improvement of outcome measurements compared to BM-MSCs.…”
Section: Cell Therapies For Cartilage Regenerationmentioning
confidence: 99%
“…3D in vitro modelling is an important technique to investigate musculoskeletal conditions as it allows cell-cell and cell-ECM interactions in 3D, mimicking the complexity of physiological tissues [47]. The 3D culture models have been attempted for bone research, especially to represent bone diseases such as OA [48,49], OP [50,51], osteomyelitis [52,53], and cancer [53,54]. Such 3D culture models representing bone led to understanding the mechanism of action of factors such as irisin, an endogenous myokine secreted during sports, which has an anabolic effect [55].…”
Section: D Models and Organoids For The Bm 41 Current In Vitro Models...mentioning
confidence: 99%